The Healing Gestures (Revista Apotheke, 2021)
"Healing Gestures" is a series of work in production that register gestures that were practiced by entities (and living ancestors) to cure.  Starting from an afro-diasporic view of a young artist inside a terreiro de umbanda, the paintings make their framings similar to photos to affirm it's function to register, bring memories and affections.
Keywords: authorial photography; memory; objects of affection; house-body; education-al action